PENGEMBANGAN FLIPBOOK DIGITAL “SAHABAT PANCASILA” BERBASIS VALUE-REFLECTIVE PEDAGOGY (VRP) UNTUK SISWA KELAS IV SDN KEMAYORAN 2 - Rifka Aidah Fatin; Devita Rizkia Ramadhani S; Mutiara Khoirus Tsani; Mujtahidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid degradation of affective character and empathy among elementary school students in the digital era poses a critical challenge to civic education. This study addresses this issue by developing a valid, practical, and effective digital flipbook learning media named "Sahabat Pancasila" based on Value-Reflective Pedagogy (VRP) to internalize the core values of the Second Sila of Pancasila. Using the ADDIE framework, the research was conducted at UPTD SDN Kemayoran 2 with 19 fourth-grade students as subjects. Data collection instruments included expert validation sheets, observation forms, and student questionnaires. The quantitative data analysis showed an average expert validation score of 95.00%, confirming that the media is highly valid and theoretically feasible. Empirical implementation through 7 operational instructional syntax of VRP achieved excellent field outcomes, including 97.50% for emotional connection, 97.00% for teacher usability, 91.80% for learning activity efficiency, and 90.47% for classical mastery of students' affective attitude development. In conclusion, the integrated VRP-based digital flipbook serves as an innovative instructional instrument to enhance students' emotional empathy and moral reasoning in primary education.